Tumbuh Kembang Bayi Optimal Dengan Mpasi Sehat - Hasanah, Neneng; Azijah, Izattul; Mawarni, Endang Siti (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2025)
Complementary feeding (MP-ASI) refers to additional foods or beverages containing nutrients that are given starting from the age of 6 to 24 months to meet nutritional needs beyond breast milk. Appropriate and proper complementary feeding is food that can meet nutritional needs so that infants and children can grow and develop optimally. The purpose of this community service activity is to educate pregnant women and mothers with babies aged 0–6 months about providing complementary feeding based on balanced nutrition to support optimal child growth and development. Evaluation of the implementation of the community service activity showed that 74% stated that the material delivered by the speaker was excellent, 62% stated that the benefits of the material were excellent, 55% rated the committee's performance as excellent, and 55% stated that access to and participation in the activity was very good.